2012
DOI: 10.1155/2012/381320
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Modulation of Na/K-ATPase Regulates Fibrosis and Renal Proximal Tubular Sodium Handling

Abstract: The Na/K-ATPase is the primary force regulating renal sodium handling and plays a key role in both ion homeostasis and blood pressure regulation. Recently, cardiotonic steroids (CTS)-mediated Na/K-ATPase signaling has been shown to regulate fibrosis, renal proximal tubule (RPT) sodium reabsorption, and experimental Dahl salt-sensitive hypertension in response to a high-salt diet. Reactive oxygen species (ROS) are an important modulator of nephron ion transport. As there is limited knowledge regarding the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 224 publications
(226 reference statements)
0
47
1
Order By: Relevance
“…We and others have previously shown that activation of the sig- naling pool of Na-K-ATPase ␣1 by cardiotonic steroids is capable of protecting the heart from ischemic reperfusion injury (11,37,38,41). On the other hand, chronic stimulation of the Na-K-ATPase/Src receptor complex by either endogenous or infused cardiotonic steroids increases the generation of reactive oxygen species and induces cardiac hypertrophy and fibrosis in vivo (14,20,21,33,35). Furthermore, replacement of endogenous ouabain-resistant ␣1 with a ouabain-sensitive ␣1 mutant increases both cardiac hypertrophy and fibrosis in pressure-overload models (49).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that activation of the sig- naling pool of Na-K-ATPase ␣1 by cardiotonic steroids is capable of protecting the heart from ischemic reperfusion injury (11,37,38,41). On the other hand, chronic stimulation of the Na-K-ATPase/Src receptor complex by either endogenous or infused cardiotonic steroids increases the generation of reactive oxygen species and induces cardiac hypertrophy and fibrosis in vivo (14,20,21,33,35). Furthermore, replacement of endogenous ouabain-resistant ␣1 with a ouabain-sensitive ␣1 mutant increases both cardiac hypertrophy and fibrosis in pressure-overload models (49).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ROS on the Na/K-ATPase enzymatic activity have been well-studied [48]. Increases in ROS and/or RNS (reactive nitrogen species) cause oxidative modification of the Na/K- ATPase α and β subunits along with FXYD proteins.…”
Section: The Interplay Of Na/k-atpase and Ros - A Positive-feedback Omentioning
confidence: 99%
“…Impairment of the Na/K- ATPase/c-Src signaling, and/or carbonylation of the Na/K-ATPase abolishes this regulation and contributes to Dahl salt-sensitive hypertension [33, 48, 56, 60, 68, 69]. Functionally, carbonylation modification of the Na/K-ATPase is implicated in renal proximal tubular sodium handling and experimental salt sensitivity [reviewed in [18, 69]].…”
Section: The Positive-feedback Amplification Loop and Experimental DImentioning
confidence: 99%
“…The assumptions necessary for this simple system of differential equations include (detailed R program shown in Appendix A):The Na/K-ATPase has a basal synthesis rate.ROS shift the Na/K-ATPase into the E2 state (as do CTS).There is a basal rate of ROS production from other sources.There is a link between Src phosphorylation and ROS production (oversimplifying the cascade, which we believe involves transactivation of the EGFR and other steps).There is a detoxification rate of ROS which is proportional to ROS concentration (an assumption that is at least partially true, based on the kinetics of superoxide dismutase and catalase).There is a relationship coupling ROS concentration to rates of endocytosis of the Na/K-ATPase [30]. …”
Section: Extension Of the Markov Chain To Define The Oxidant Amplimentioning
confidence: 99%